E-194 Patient-specific hemodynamics predict endovascular coiling outcomes for intracranial aneurysms. (4th August 2020) - Levy, S; Marsh, L; Barbour, M; Prijoles, K; Lim, D; Haughn, H; Kelly, C; Chassange, F; Barros, G; Bass, D; Aliseda, A; Levitt, M; et al.
Abstract : Introduction: Embolic coils are a preferred endovascular treatment technique for intracranial aneurysms, but approximately 34% of these treatments are unsuccessful, requiring re-treatment. To better understand why endovascular treatment fails, we used computational fluid dynamics (CFD) simulations to determine the changes in hemodynamics factors after coil embolization that were associated with treatment success versus those that led to failure. We incorporated patient-specific intravascular blood flow measurements as boundary conditions, which has been shown to improve simulation accuracy. Materials and Methods: Adult patients presenting with unruptured intracranial aneurysms treated with coil embolization were enrolled. 3D-rotational angiograms taken before and immediately after treatment were used to create computational models of the patients' vasculature. Intraoperative blood velocity and blood pressure measurements were obtained before and immediately after coil embolization by placing a dual-sensor microwire (ComboWire) in the proximal segment of the parent vessel. These measurements were incorporated as patient-specific boundary conditions for the CFD simulations to compute hemodynamics conditions before and after treatment. Hemodynamics variables including inflow rate (Q), wall shear stress (WSS), and wall shear stress gradient (WSSG) were calculated within each aneurysm. Treatment success or failure was determined by evaluating each patient's most recent follow-up angiogram, and this outcome was then correlated to the changes in hemodynamics variables pre- and post-treatment. This statistical analysis aims to determine associations between immediate changes in post-treatment hemodynamics variables and treatment outcomes. Results: Sixteen patients were included (table 1 ). Regardless of long-term treatment outcome, immediate post-treatment reductions were observed in Q, WSS and WSSG. Preliminary analyses suggest that an increase in shear stress at the aneurysm neck was associated with successful long-term outcome, representative of the significant redirection of blood flow velocity by the coil mass required to prevent aneurysm recanalization. Final multivariate analyses will be presented. Conclusion: CFD simulations of aneurysm hemodynamics using patient-specific imaging and boundary conditions were performed in a large cohort of patients treated with coil embolization. Increases in neck plane shear and redirection of blood flow found immediately post-coil embolization have the potential to predict long-term treatment success. Disclosures: S. Levy: None. L. Marsh: None. M. Barbour: None. K. Prijoles: None. D. Lim: None. H. Haughn: None. C. Kelly: None. F. Chassange: None. G. Barros: None. D. Bass: None. A. Aliseda: None. M. Levitt: 1; C; Philips Volcano. L. Kim: None.